Gambaran Bullying pada Remaja di Boarding School Kota Banda Aceh - Ridwan, Arfiza; Ahad, Fazal; Diba, Farah (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
Background. One of the phenomena that can be of concern in the world of education is the case of bullying in schools. Bullying can occur in public schools, but boarding schools are potentially more vulnerable because students spend more time together Objective. to feature the bullying behaviour among adolesce in Banda Aceh. Methods. his research design is a cross sectional study. The sampling technique used proportionate random sampling with a total sample size of 236 students. The data collection tool is a questionnaire consisting of 39 questions in the form of a bullying scale by means of a questionnaire. Data were analyzed using frequency distribution Results. The analysis shows that the level of bullying in boarding school students in Banda Aceh City, which is in the low category, 98.7% do not experience bullying and those in the high category are 1.3%. Conclusion. The research shows that bullying still occurs in boarding schools, although it only involves a small proportion of students who experience bullying.